Mud-shrimps of the genus Axianassa Schmitt, 1924 from Panama, with description of two new species (Decapoda: Gebiidea: Laomediidae) - Anker, Arthur; Pachelle, Paulo P.g. (Zootaxa, 2016)
Six species of the mud-shrimp genus Axianassa Schmitt, 1924, herein placed in the Laomediidae, are reported from Panama, five species from the Pacific coast and one species from the Caribbean coast. Axianassa mineri Boone, 1931 and A. canalis Kensley & Heard, 1990, both originally described from the Pacific coast of Panama, are reported from new Panamanian localities, with the former species also reported from a new locality on the Pacific coast of Mexico. Additional illustrations complete the original descriptions of these two species. The recently described A. darrylfelderi Anker & Lazarus, 2015, previously known only from the type material from the Pacific coast of Colombia, is reported for the first time from Panama, whereas A. jamaicensis Kensley & Heard, 1990, previously known only from Jamaica, is reported for the first time from the Caribbean coast of Panama. Two species, viz. A. linda sp. nov. and A. christyi sp. nov., are described as new based on material from the Azuero Peninsula and the Las Perlas Archipelago, on the Pacific coast of Panama. Colour photographs are provided for all six species. A revised key to the 13 presently known species of Axianassa is provided, in addition to some taxonomic remarks on the genus and a justification for its placement in the family Laomediidae rather than Axianassidae.